Migration and human capital accumulation in China - John Giles; Yang Huang (IZA World of Labor, 2020)
The difference in educational attainment between China's urban- and rural-born populations has widened in recent years, and the relatively low educational attainment of the rural-born is a significant obstacle to raising labor productivity. Rural-to-urban migration does not create incentives to enroll in higher education as the availability of low-skill employment in urban areas makes remaining in school less attractive. In addition, the child-fostering and urban schooling arrangements for children of migrants further inhibit human capital accumulation.
Keywords: 330; migration; human capital; China